Caracterización clínica de tumores mamarios en hembras caninas de la ciudad de Loja - Ordoñez Benítez, Martha Julia (2024)
A canine mammary tumor (CMT) represents the most prevalent form of neoplasia in dogs. Their evaluation requires a comprehensive assessment of several risk factors, including breed, age and reproductive status, as well as tumor-specific characteristics such as type, size, location and evidence of metastatic. Correct clinical staging plays a critical role in determining the extent of cancer, enabling effective clinical management and the development of appropriate treatment strategies. The aim of this study is to clinically characterize mammary tumors in female dogs from Loja city, focusing on their anatomopathological features and the detection of metastatic sites. The study included 11 female dogs with mammary tumors evaluated at the Cesar Augusto Guerrero Veterinary Teaching Hospital, part of the National University of Loja. Specifically, clinical staging is conducted according to the World Health Organization (WHO) TNM system, which examines tumor size and spread, lymph node involvement and the presence of distant metastatic. In this study, 54.54% of tumors are solitary masses and 81.81% are attached to the skin. The most common tumor size is classified as T1 (< 3 cm), accounting for 54.54% of cases. The caudal abdominal mammary glands are most commonly involved (63.63%), with the right chain of mammary glands most commonly involved (54.54%). All tumors had a firm consistency and hyperpigmentation and ulceration are observed in 63.63% of the tumors. No secondary tumors or metastatic foci are detected in any of the animals. A total of 54.54% are classified as stage I, 27.27% as stage III and 18.18% as stage II. These results highlight the importance of staging by anatomopathological evaluation and detection of metastatic in routine clinical practice.